2020
DOI: 10.1016/j.jmarsys.2020.103449
|View full text |Cite
|
Sign up to set email alerts
|

Body size and stable isotope composition of zooplankton in the western tropical Atlantic

Abstract: Size-based approaches are paramount tools for the study of marine food webs. Here, we investigated the relationship between zooplankton body size, stable isotope composition and trophic level (TL) along a large-scale onshore-offshore gradient in the western tropical Atlantic. Samples were obtained on the Brazilian continental shelf, slope and in oceanic waters (off Fernando de Noronha archipelago and Rocas Atoll) in September and October 2015. Zooplankton was sieved into five size fractions. Zooplankton was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 69 publications
3
7
0
Order By: Relevance
“…In the Mediterranean Sea, Romeo et al (2016) observed similarities in the size of MPs and the size of the copepods, prey of lanternfishes, suggesting active and selective ingestion of MPs. We observed a similar pattern, as the dimensions of the MPs found in the SWTA were similar to those of common prey of the species (<2 mm), e.g., amphipods and fish larvae in this region (Figueiredo et al, 2020). Through experiments, Li et al (2021) demonstrated that fish could capture MPs passively by breathing but that some of them are also ingested inadvertently due to the similarity between their prey or the tiny sizes, which are hard to distinguish.…”
Section: Discussionsupporting
confidence: 62%
“…In the Mediterranean Sea, Romeo et al (2016) observed similarities in the size of MPs and the size of the copepods, prey of lanternfishes, suggesting active and selective ingestion of MPs. We observed a similar pattern, as the dimensions of the MPs found in the SWTA were similar to those of common prey of the species (<2 mm), e.g., amphipods and fish larvae in this region (Figueiredo et al, 2020). Through experiments, Li et al (2021) demonstrated that fish could capture MPs passively by breathing but that some of them are also ingested inadvertently due to the similarity between their prey or the tiny sizes, which are hard to distinguish.…”
Section: Discussionsupporting
confidence: 62%
“…These results lead us to hypothesize that in regions where the thermocline is 215 highly stratified, and less mixed, some organisms avoid the layer of highest gradient. These results agree with previous studies (Lee et al, 2013) and are also consistent with the fact that, in the SECS in spring, zooplankton biomass is lower than in the WBCS, but organisms are larger (Figueiredo et al, 2020). Larger zooplankton are more likely to inhabit greater depths under more stratified conditions (Hampton et al, 2014).…”
supporting
confidence: 92%
“…This pattern is likely driven by the local food availability, as the study area includes several coral reefs, islands, and seamounts that could enhance the larval abundance of several species (CBD, 2014). Indeed, a recent study addressing zooplankton communities in the same location highlights a high biovolume of fish larvae in sample size fractions larger than 2000 µm (Figueiredo et al, 2020). Local differences in food availability also seem to reflect the trophodynamics between myctophids and their potential predators.…”
Section: Vertical Migration Trophic Ecology and Niche Partitioningmentioning
confidence: 99%
“…Additionally, our results revealed differences in the oxygen and fluorescence profiles of these areas. Together, all these oceanographic features resulted in significant variations in zooplankton biomass (Figueiredo et al, 2020) and planktonic cnidarian composition (Tosetto et al, 2021).…”
Section: Species Richness and Dominance Patternsmentioning
confidence: 99%